(Divorce in the Palestinian society and its relation to some variables from the point of view of divorced women in the city of Ramallah during the period (2010- 2019 - Alawneh, Abd Elmajid Naief (Journal of Humanities & Social Sciences, 2019)
This study is a critical analytical study in which the researcher used the analytical descriptive approach to describe the previous studies in this subject. In addition, he dealt with the field aspect which is represented by selecting the research society, the divorced women in the Palestinian city of Ramallah, using the questionnaire tool, In the study of these cases of divorced women, where the aim of this research in dealing with the problem of divorce in the Arab Palestinian society, especially after the knowledge of the increased presence of this phenomenon in recent years, the researcher studied the impact of factors that affect the increase This phenomenon was dealt with in two parts: the main theoretical section in this research in an analytical and critical manner based on the previous studies, in addition to a field social study on a sample of divorced women in the city of Ramallah in the middle of the West Bank. This research led to a number of results. The most important of these results was that the divorce rate has been high in recent years for many reasons, especially the unconscious and insufficient awareness, in addition to the existence of social diseases and the absence of social democracy within the family itself, Other factors, cultural, economic and social Kaltgar. It also emerged that cultural change is the most influential on the rise of divorce cases followed by economic change and social change, where it was found that the first place in the impact on the rise of divorce came to the cultural change, which reached the degree of impact to the value of (87%) followed by second place in the degree The impact on the rise of divorce cases in the Palestinian society for economic change, which was 69%, while the degree of impact of social change in the impact on the increase in divorce in this community to a value of only 30% Cultural and economic, The majority of divorced women were younger than 30 years of age (68%), non- women or single- parent children (83%) with a low level of education, (68%). Most of them do not work permanently (68%) and have an average monthly income or less (87%). It was found that there is a strong and inverse and statistically significant relationship between reproduction, educational level and income levels. The higher the number of divorces, the higher the number of children, the educational level and level Monthly income less divorce rate and vice versa. At the end of this research, the researcher made a number of recommendations at the public and private levels, the most important of which was the introduction of an orientation course for those who are coming to marriage and the necessity of alerting the media about the dangers of this phenomenon in different aspects. In terms of lifestyles, procreation and others.
Keywords: divorce; society; variables; divorced women